Antiplasmodial Activity of Psidium guajava L. Leaf Fractions against Plasmodium falciparum - Ahmad Saidu; Yusuf Hassan; Abubakar Sani (Pharmaceutical Reports, 2026)
Malaria remains a major global health challenge, particularly in sub-Saharan Africa, where resistance to conventional antimalarial drugs continues to rise. This study aimed to evaluate the in vitro antiplasmodial activity of Psidium guajavaL. leaf fractions against Plasmodium falciparum. Dried leaves were extracted using ethanol and subsequently fractionated into n-hexane, chloroform, ethyl acetate, and ethanol fractions. Phytochemical screening using standard reagents revealed the presence of alkaloids, flavonoids, terpenoids, and saponins in all fractions, while tannins were detected only in the ethyl acetate and ethanol fractions. Antiplasmodial activity was assessed using the Giemsa staining method. All fractions demonstrated concentration-dependent inhibition of parasite growth, with the ethanol fraction exhibiting the highest activity, achieving 84.38% inhibition at a concentration of 10.5 mg/mL. This activity was comparable, although slightly lower, than that of the standard drug artemether/lumefantrine, which showed 95.31% inhibition. The superior activity of the ethanol fraction is likely attributed to its higher content of polar bioactive compounds, particularly flavonoids and tannins, which are known for their antiplasmodial properties. In conclusion, P. guajava leaf fractions, especially the ethanol fraction, exhibit significant antiplasmodial activity, supporting their traditional use in malaria treatment. These findings highlight the potential of P. guajava as a promising source of natural antimalarial agents and warrant further pharmacological and mechanistic studies.